Edukasi Deteksi Dini Kanker Servik Melalui IVA Tes Kelurahan Menteng Kecamatan Medan Denai Tahun 2024 - Simarmata, Mesrida; Padilla Siregar , Erin; Rezeki , Sri; Simanjuntak, Lisdayanti; Azizah, Nur; Elvi Yesya, Sri; Azzahra, Latifa; Srininta Srininta (Jurnal Informasi Pengabdian Masyarakat, 2024)
Cervical cancer is a malignant condition that occurs in the cervix. Cervical cancer is ranked in the world and 10th in developed countries. In Indonesia, 90-100 cases per 100,000 population. 92% of clinical manifestations of pre-cancerous lesions are asymptomatic. So community service is carried out. Title: Education on Early Detection of Cervical Cancer through Visual Inspection of Acetic Acid (IVA Test) in Women of Childbearing Age in Ward IV, Menteng Village, Medan Denai District, Medan City, North Sumatra Province in 2024. Objective: To help WUS Menteng Medan Denai in increasing knowledge about cervical cancer , early detection through IVA tests, screening indications, outcome categories, and growing interest in WUS for early detection of cervical cancer. Participants: WUS Ward IV, Menteng Village, Medan Denai District, Medan City. Time and Place: July – September 2024 at Environmental Madrasah IV, Menteng Village, Medan Denai District, Medan City. The method used was a lecture and measuring the understanding of community service participants before and after regarding early detection of cervical cancer. Results: before the education was carried out about Visual Inspection of Acetic Acid (IVA Test), the majority was less than 15 people (50%), but after the education was carried out there was an increase in knowledge, the majority was good at 20 people (67%). Conclusion: Education regarding early detection of cervical cancer through the IVA test is effective in increasing knowledge of WUS in Environment IV, Menteng Village, Medan Denai District.